(untitled) (Global Media Journal - German Edition, 2017)
Based on a secondary analysis of representative survey data of journalists in Germany (n= 1536), this paper draws attention to two variables that are important when it comes to explain whether journalists accept questionable reporting practices, such as paying people to obtain information or using confidential government documents without permission. First, perceived role achievement is important, as journalists who do not feel able to achieve an active role tend to accept questionable reporting practices more often. Second, however, this relationship is only true for journalists having a moderate tendency to the political left. Findings are explained by means of the theory of cognitive dissonance.